Labor supply responses to adverse shocks under credit constraints evidence from Bukidnon, Philippines - Malapit, Hazel Jean; Redoblado, Jade Eric; Dolor, Deanna Margarett Cabungsal; Suministrado, Jasmin ([Quezon City] School of Economics, University of the Philippines, 2008)
The ability of households to insure consumption from adverse shocks is an important aspect of vulnerability to poverty. The most vulnerable households are those with little education and with few or no able-bodied male members. Appropriate policy responses include countercyclical workfare programs directed at households with high female-to-male ratios, households with high dependency ratios, and households with little or no education, as well as the provision of universal education and health care.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (pages 84-86)
Keywords: Labor supply -- Philippines -- Bukidnon; Consumption (Economics) -- Philippines -- Bukidnon